2001
DOI: 10.2337/diabetes.50.12.2858
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c Levels Are Genetically Determined Even in Type 1 Diabetes

Abstract: 5-28]). Multivariate modeling showed that genetic factors also have a substantial influence on fasting glucose levels (51%). However, HbA 1c heritability could not be explained by genes in common with fasting glucose. In the patients with type 1 diabetes, HbA 1c levels were correlated in 33 MZ twins concordant for diabetes (r ‫؍‬ 0.68; P < 0.001) but also in 45 MZ twins discordant for the disease (r ‫؍‬ 0.52; P < 0.001). These significant correlations for HbA 1c in both concordant and discordant pairs indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
115
2
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(123 citation statements)
references
References 29 publications
(20 reference statements)
3
115
2
3
Order By: Relevance
“…First, they demonstrate a contrast between GSPs, which are not inherited, and A1C, which is inherited. This observation limits the range of candidate mechanisms that could account for the heritability of A1C (9). Second, these findings demonstrate that a measure, the GG, which captures the variation of A1C in a population beyond that which is attributable to blood glucose variation, also captures a proportion of the heritability of A1C based on quantitative genetic modeling.…”
Section: Quantitative Genetic Model Fittingmentioning
confidence: 85%
See 1 more Smart Citation
“…First, they demonstrate a contrast between GSPs, which are not inherited, and A1C, which is inherited. This observation limits the range of candidate mechanisms that could account for the heritability of A1C (9). Second, these findings demonstrate that a measure, the GG, which captures the variation of A1C in a population beyond that which is attributable to blood glucose variation, also captures a proportion of the heritability of A1C based on quantitative genetic modeling.…”
Section: Quantitative Genetic Model Fittingmentioning
confidence: 85%
“…McCarter et al (8) found that HGI was likewise reproducible over time and that retinopathy and nephropathy risk were predicted by the HGI determined on numerous extended capillary glucose profiles throughout the duration of the Diabetes Control and Complications Trial. Evidence from both healthy and diabetic twins indicates that A1C levels are genetically determined, which provides an independent line of evidence that A1C is in part determined by factors other than glycemic control (9). Given the two independent lines of evidence about A1C variance and heritability (7-9), a logical question that arises is whether the heritable components of A1C are associated preferentially with the GG fraction or the GSPs fraction of the A1C variance, as this would narrow the range of mechanisms involved and inform candidate gene studies.…”
mentioning
confidence: 84%
“…46,47 Whereas some authors interpret data as indicating minimal biologic variation in HbA1c between individuals, 4 others have found evidence for more marked differences resulting from poorly understood genetic factors. 48,49 After the elucidation of the nature of nonenzymatic glycation, 50,51 glycation rates have been shown to be subject to variation between individuals by factors that are independent of glucose concentration, including pH, 32 inorganic phosphate, 52 oxidative stress, 53 deglycation, 43,54 and Schiff base inhibitors. 55 These techniques used here, in combination with frequent blood glucose sampling, could evaluate the importance of these factors.…”
Section: Hba1c Synthesis Ratementioning
confidence: 99%
“…The heritability estimate shows how much of the phenotypic variance is attributable to the average effects of genes [6]. For fasting glucose, heritability studies in Northern Europe have mostly been done using twin registers, in which heritability estimates ranged from 38 to 51% [7][8][9]. Heritability estimates tend to be higher among twins than in extended pedigrees because of greater similarities in early-life environment and behavioural patterns among twins.…”
Section: Introductionmentioning
confidence: 99%